Mulligan Manipulation Combined with Mckenzie Mechanics Method in Treating 43 Cases of Cervical Spondylotic Radiculopathy - Fuchun WU; Jie CHEN; Wei XU; Guoqing MO (康复学报)
Objective:To observe the curative effects of Mulligan manipulation combined with Mckenzie mechanics method for the treatment of cervical spondylotic radiculopathy (CSR).Methods:A total of 86 CSR patients were assigned to the treatment group and the control group by a random number table, and 43 patients in each group. Two groups received the basic physical therapy, such as cervical traction and ultrashort wave therapy. The treatment group was added with Mulligan manipulation and Mckenzie function training, and the control group was added with traditional Chinese medicine manipulation. One time per day and every ten times was a course of treatment. Some measurements including pain visual analog scale (VAS), clinical assessment scale for cervical spondylosis (CASCS), the MOS Item Short From Health Survey (SF-36) were recorded to evaluate the curative effects before and after the treatment.Results:The VAS scores in the two groups were decreased after the treatment (P<0.01), and the decreasing amplitude of treatment group was higher significantly than that of the control group (P<0.05); the scores of CASCS and SF-36 in the two groups were increased after the treatment (P<0.01), and the increasing amplitude of treatment group was higher significantly than that of the control group (P<0.05); there were significant differences in cure rate and total effective rate between the two groups (P<0.01).Conclusion:On the basis of cervical traction and ultrashort wave therapy, Mulligan manipulation combined with Mckenzie function training has positive effects on the improvement of the symptoms, signs and functional status and the quality of life for CSR patients.